Analysis of the impact of the board of directors as a central governance body on the performance of Moroccan banks - Yassine , NAKI; EL BAKKOUCHI , Mounir (Revue du contrôle, de la comptabilité et de l’audit, 2023)
This study aims to analyze empirically the impact of the board of directors as an internal governance mechanism on the performance of Moroccan banks, based on its various roles and, above all, the specific features of bank governance. Empirical validation is obtained by econometric modelling using panel data constructed from 6 Moroccan commercial banks listed on the Casablanca stock exchange and observed for a period of 10 years, from 2012 to 2021. We attempt to detect the impact of bank governance characteristics, through the study of board structure, on bank performance. Our results show the absence of a significant link between the characteristics of the Board of Directors and the performance of Moroccan banks expressed by ROA and ROE. On the other hand, the size of the bank and the capital have a negative impact on the ROA of the banks in our sample. Our study also shows a negative and significant relationship between ROE and bank size.